Women’s Contribution to Urban Governance in the Municipalities of Greater Lomé - Dounwourgue, Nagbandjoa; Kola, Edinam (Journal of Ecohumanism, 2025)
This paper analyses, in the specific context of Togo, the contribution of women to urban governance in the municipalities of Greater Lomé, which is characterised by a dynamic of decentralisation and growing citizen participation. Although women play a central role in society, their formal involvement in urban decision-making processes remains limited, particularly due to restrictive sociocultural norms, lack of access to training and information, and the absence of specific institutional support to strengthen their engagement. The study adopts a mixed methodology combining quantitative surveys of women and men living in the municipalities of Greater Lomé, semi-structured interviews with key actors such as local elected officials, NGO managers and community leaders, as well as a documentary analysis of the legislative and institutional frameworks governing urban governance in Togo. The results show that the involvement of women in governance is constantly increasing, even though they are affected by sociocultural influences that limit their participation in decision-making processes. However, the article emphasises that local initiatives are bearing fruit, particularly in certain municipalities where programmes to strengthen women’s capacities are being implemented. To strengthen the contribution of women in the urban governance of the municipalities of Greater Lomé, this study recommends eliminating structural and sociocultural barriers, improving access to training for women, and creating an institutional environment that supports their involvement in governance processes.